Low LATS2 expression is associated with poor prognosis in non-small cell lung carcinoma - Jang, Si-Hyong; Oh, Mee-Hye; Cho, Hyun; Lee, Ji-Hye; Lee, Hyun; Ahn, Hyein; Kim, Han (Polish Journal of Pathology, 2019)
Large tumor suppressor kinase 2 (LATS2) is a core component in the Hippo signaling pathway, and it functions as a tumor suppressor associated with tumor cell proliferation and apoptosis. The purpose of this study is to explore LATS2 expression and its clinicopathological significance in non-small cell lung cancer (NSCLC). We examined LATS2 protein expression by immunohistochemistry in 184 resected NSCLC specimens using tissue microarrays. Low LATS2 expression was significantly related to disease recurrence (p = 0.047). In survival analysis, the low LATS2 expression group showed a statistically poorer overall survival (OS) (p = 0.004) and disease-free survival (DFS) (p = 0.014) than the high expression group. In multivariate analysis, downregulated LATS2 expression in NSCLC could be an independent prognostic factor of poor OS and DFS. Furthermore, we evaluated the prognostic significance of LATS2 expression in two major NSCLC subtypes, squamous cell carcinoma and adenocarcinoma. The low LATS2 expression group showed worse prognosis than the high LATS2 expression group (OS [p = 0.144] and DFS [p = 0.022] in squamous cell carcinoma and OS [p = 0.045] and DFS [p = 0.271] in adenocarcinoma). We demonstrated that downregulated LATS2 expression may predict aggressive biologic behavior and a worse prognosis in NSCLC and we also suggested the possibility of LATS2 as a therapeutic target in both squamous cell carcinoma and adenocarcinoma.